Mengukur Tingkat Keterikatan Masyarakat Kampung Atas Air, Kota Balikpapan - Devi Triwidya Sitaresmia; Mohtana Kharisma Kadrib; Rahmi Yorika; Rina Noor Hayati (Jurnal Pembangunan Wilayah dan Kota, 2021)
This research originated from the theory of community attachment based on social relationships which can cause emotional feelings towards their place of residence as a result of their journey of living together. There is also the term Gemeinschaft (intimate community) for people who know each other and develop so that they have a sense of density, friendship, and personal emotional bonds between them. One of the living environments that is characterized by gemeinchaft is the urban hometown. The urban village is an informal village, unplanned and not served by adequate housing infrastructure. One of the efforts made by the government to improve the quality of urban villages is through the Community-Based Settlement Environmental Management (PLPBK) program. The village over the water of Kelurahan Baru Tengah is one of the areas targeted by the PLPBK program. This program is a program to improve the quality of the settlement environment using a participatory approach, so that the role of the community is very important in its implementation. This study aims to determine the level of community engagement in urban village settlements, namely Kampung Atas Air, Baru Tengah Village, using Social Network Analysis (SNA). This paper shows that the level of community engagement in Kampung Atas Air, Baru Tengah Village is high. The high level of community engagement is expected to become social capital that can support community-based government programs.